Randomized Trial of Robot-Assisted Rehabilitation for Chronic Stroke - Sinclair, Heather Q. (MD Conference Express, 2010)
Robot-assisted therapy (RT) and intensive comparison treatment, structured to match that of RT with regard to number of sessions, type, and intensity of movement, were superior to customary chronic poststroke care (usual care — UC) for the treatment of chronic stroke that affected the upper extremities. This article discusses the use of novel RT as a rehabilitation strategy to improve functionality and quality of life in patients =6 months poststroke.